MENDUDUKAN WACANA GENDER (Dari Kesalahpahaman Menuju Pemahaman) - Indrayati, Susi (MUWAZAH, 2012)
Abstract : Departing from the public misunderstanding of the concept is identical to the female gender, the study intends seats the gender discourse (concepts and theories) that misunderstanding into understanding. To understand the concept of gender would not be separated from an understanding of the concept of sex, because it will cause an error in the understanding of gender inequality such as stereotyping, discrimination, subordination, marginalization, and the double burden of violence against women. Gender theory becomes important for an operation in this context, as in the context of understanding the reality of seats the history and thought that from experts and Kulture tersebutlah gender discourse was born and of course to provide a deeper understanding of the extremities in order not to get caught up in the flow of the ideology or gender. Abstrak : Berangkat dari kesalahpahaman umum  tentang konsep yang diidentikan dengan jenis kelamin perempuan, tulisan ini bermaksud mendudukkan wacana gender (konsep dan teori) dari sebuah kesalahpahaman menjadi sebuah pemahaman. Memahami konsep gender, saesungguhnya tidak akan lepas dari pemahaman tentang konsep seks, karena akan menyebabkan kesalahan dalam memahami ketidakadilan gender seperti stereotip, diskriminasi, subordinasi, marginalisasi, dan beban ganda kekerasan terhadap perempuan. Teori gender menjadi penting dalam konteks ini, seperti dalam konteks memahami realitas sejarah agar tidak terjebak dalam aliran ideologi gender yang keliru